112k views
0 votes
Balance the equation: FeSO4(s) + O2(g) + H2O(l) = Fe(OH)3 + H2SO4

User SerMetAla
by
5.3k points

1 Answer

1 vote

Answer: 4 FeSO4(s) + O2(g) + 10 H2O(l) ---> 4 Fe(OH)3 + 4 H2SO4

Explanation:

FeSO4(s) + O2(g) + H2O(l) = Fe(OH)3 + H2SO4

In other to balance the equation, the total number of atoms of each element on the Left Hand Side (LHS) of the equation must be equal to the total number of atoms on the Right Hand Side (RHS) of the equation.

Add the following coefficients to the equation;

FeSO4 = Add 4, H20 = Add 10, Fe (OH)3 = Add 4 and H2SO4 = Add 4

By doing this, you will discover that the total number of atoms on bothe sides of the equation are balanced; thus we have;

4 FeSO4(s) + O2(g) + 10 H2O(l) ---> 4 Fe(OH)3 + 4 H2SO4

User Amit Mohanty
by
6.2k points